Introducing the ECB indicator on euro area industrial new orders - Gabe de Bondt; Heinz Christian Dieden; Sona Muzikarova; Istvan Vincze (European Central Bank (ECB), 2013)
Following the discontinuation of the official statistics on industrial new orders by Eurostat in mid-2012, this paper introduces the ECB indicator on euro area industrial new orders, which aims to fill the new statistical gaps for euro area total new orders as well as for various breakdowns. Despite the discontinuation of the data collection at European level, a large number of euro area countries are expected to continue with the data collection nationally. For those countries which have discontinued the collection of national data, model-estimates are used in calculating the ECB indicator on euro area industrial new orders. New orders are modelled across EU countries using “soft” data (business opinion surveys) as well as “hard” data (industrial turnover) and applying a common modelling framework. The model determinants significantly explain the monthly growth rates in new orders across approximately 200 estimated equations. Various tests show that the estimates are robust. This paper demonstrates that, besides the leading information content of industrial new orders for euro area industrial production, the monitoring of the ECB indicator on new orders is useful for cross-checking developments in industrial production in real time.
Keywords: E10; E13; E17; 330; ECB indicator; euro area; Industrial new orders; leading indicators; real-time analysis; Wirtschaftsindikator; Auftragseingang; Industrieproduktion; Eurozone